Ankle Hemodynamic Index to Assess the Severity of Peripheral Arterial Disease Compared to Ankle Brachial Index - Rimon Tharwat Sabry, Mohamed Awad Taher, Hany Mohamed Awadalla, Sherif Essam Tawfik, Mohamed Moustafa Farouk (Pakistan Journal of Medical & Health Sciences, 2022)
Aims: The goal of this study is to assess the diagnostic efficacy of the “ankle-brachial index, ankle hemodynamic index (Tanno et al, 2016) correlated with the Rutherford grading of lower limb ischemia” in patients with angiographically proven peripheral artery disease as assessed by either CT or contrast angiography of the lower extremities as imaging modalities. Methods: This observational cross-sectional study included 100 participants with proven peripheral artery disease who were referred to Nasr city health insurance hospital’s vascular department and outpatient clinic. Results: Study participants ranged in age from 35-86. The mean age of the participants was 63.6 ± 10.5 years. They were 70 males (70%) and 30 females (30%). The ankle-brachial index value ranged from 0.6 up to 1.3 for all of the participants that were evaluated, with a mean of 1 and a standard deviation of 0.2. Ankle hemodynamic index ranged from 17 to 73, with 17 being the lowest possible value and 73 being the highest possible value. The mean ankle hemodynamic index was 41.2 ± 13.4. Ankle hemodynamic index and Rutherford grade have an extremely statistically significant positive correlation. Conclusion: In conclusion, the AHI was shown to be substantially positively connected with the severity of PAD as assessed by Rutherford grading, but the ABI was found to be non-significantly associated with Rutherford grading. We also discovered that Rutherford grade was linked to HbA1C, Hb, CRP, and ankle DBP.